A natureza e a criança: uma relação essencial para o desenvolvimento infantil - Vellozo, Letícia Munhoz (2022)
This research addresses the theme of environments and natural elements as one of the structuring axes of educational practice in early childhood education and the teaching and learning process of children, and aims, through participant observation, to show how children appropriate these environments and elements in daily life and school practices. This research intends to answer the question: Understand which environments and natural elements are part of a kindergarten school in São Carlos and how they are explored by children and by the educational practice present in the school routine. In order to do so, it sought in theoretical references, contributions from authors who discuss the importance of nature in early childhood education, as well as Brazilian documents for this type of education that reinforce outdoor experiences, both references maintain that environments and natural elements are fundamental, among other things, for the development of creativity, imagination and ecological awareness. In addition, considering that the child's main activity is play, as well as its creative re-elaboration, being in natural environments and enjoying its elements expands the possibilities of play and creation, stimulating curiosity, inspiring new discoveries and developing different ways of thinking. So, this research with a qualitative approach sought, through participant observation, to collect data in an early childhood school in São Carlos, in the interior of São Paulo, with children aged four and five. The insertions were for two hours a day for 18 days at different times of the school routine and the data were organized into observation journals and photographs. It is worth noting that the research took place during the COVID-19 pandemic, so there were some complications during the collection. The data were analyzed according to the Content Analysis proposed by Bardin (2016) and divided into three categories: Fauna and flora of the school environment, Elements of nature (water, earth, air and fire) and Natural elements (sticks, stones, seeds, leaves, etc.). However, when the school environment is thought collectively and allows the child to have contact with the external environment, it provides opportunities for experiences, challenges, curiosity, creativity and autonomy, in addition, this contact with nature allows the child to relate, be enchanted and become aware of caring for the Earth, awakening ecological awareness and the formation of more conscious and responsible adults.